Solar-Light-Driven N-TiO2-SiO2 Photocatalytic Activity on the Simultaneous Removal of Bisphenol-A and Escherichia coli - Le, Minh Vien; Tran, Trung Tan; Hoang, Anh Hoang; Nguyen, Hien Thao; Le, Vu Truong-Son; Luan, Van Hoang; Ngo, Manh Thang (Universitas Gadjah Mada, 2025)
N-doped TiO2-SiO2 nanocomposites were synthesized using a facile sol-gel method and characterized through various techniques. Their photocatalytic performance was assessed by degrading BPA (10 mg L−1) and inactivating Escherichia coli ( 109 CFU mL−1) under single and dual contaminant conditions using a 26 W solar light simulator. Among the synthesized materials, the N-TiO2-SiO2 nanocomposite with a 10% N:Ti molar ratio (TS5N10) demonstrated the highest photocatalytic activity, achieving 83.9% BPA degradation and complete E. coli disinfection in single contaminant systems after 4 h of irradiation. Notably, TS5N10 exhibited robust performance even in dual-contaminant scenarios involving BPA and E. coli. Mechanistic investigations identified photo-generated holes as the dominant reactive species. The superior performance of TS5N10 was attributed to its nanostructure, high specific surface area, strong light absorption, and reduced photoinduced electron-hole recombination. These results highlight the potential of TS5N10 for practical water treatment applications.